World financial orders : an historical international political economy - Langley, Paul, 1972- (Routledge/RIPE series in global political economy. Routledge/RIPE studies in global political economy, 2002)
This book challenges the predominance of neo-liberalism as a mode of knowledge about contemporary world finance, and claims that it neglects the social and political bases as well as the malign consequences of change.